Analisis Perbandingan Perilaku Konsumen Dalam Pengambilan Keputusan Berbelanja Di Toko Madura dan Minimarket Di Kabupaten Bangkalan - Hotijah, Hotijah; Septiana, Aldila (Universitas Negeri Surabaya, 2024)
This research aims to determine differences in consumer behavior in making shopping decisions at Madura Stores and Minimarkets in Bangkalan Regency. This type of research is quantitative research. The population in this research is all consumers who shop at Madura Stores and Minimarkets in Bangkalan Regency, an unknown number. Meanwhile, for the sample in this study, researchers used 50 respondents. The data collection techniques used were questionnaires and observation. Data analysis techniques in this research used validity tests, reliability tests, Kolmogov-Smirnov normality tests, and paired sample t-tests using IBM SPSS 23. Based on the results of research that has been carried out, it is known that there is no significant difference between consumer behavior in making shopping decisions at Madura Stores and Minimarkets in Bangkalan Regency. With this information, it is hoped that it will be able to provide insight to the entire community in making policy decisions regarding the existence of Madura Shops and Minimarkets for shopping for necessities.